-2x+2=-5+16

Simple and best practice solution for -2x+2=-5+16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x+2=-5+16 equation:


Simplifying
-2x + 2 = -5 + 16

Reorder the terms:
2 + -2x = -5 + 16

Combine like terms: -5 + 16 = 11
2 + -2x = 11

Solving
2 + -2x = 11

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + -2x = 11 + -2

Combine like terms: 2 + -2 = 0
0 + -2x = 11 + -2
-2x = 11 + -2

Combine like terms: 11 + -2 = 9
-2x = 9

Divide each side by '-2'.
x = -4.5

Simplifying
x = -4.5

See similar equations:

| 12y^2=5y+3 | | 1.86g-10=0.23 | | 2x+3x+100=180 | | 5(0.45)=1.70 | | -24*4-53=39-4 | | 4b-3-8b-9= | | f=1.8c+32+16 | | x+59=69 | | 3x-1=40 | | 4x-6+22=7 | | 1=2k | | 5(2x-3)-2(x+1)=x-4 | | 5z-7=23 | | 5z-7= | | ln(x+5)-Ln(x-1)=-ln(x+1) | | 10=3+e | | 2x^2+3x=16x+7 | | -18=x-18 | | -8x+30=10 | | 6-2(3-2x)=-4(3-x) | | -5d=10 | | z-4(z+2)=3(z-4)-2z | | 4(x+2)=14+-2(3+4x) | | -2(6-3x)=-12+6x | | 2m^2+15m+25=0 | | -5d=19 | | 4a-5=29-3 | | 4(9x+2)-5(3+4x)=0 | | -6+k=18 | | 14x-48=x^2 | | 6(x-3)+10=6x-8 | | 3/2-6+5/2=4t+2 |

Equations solver categories